1988
DOI: 10.1364/ao.27.002502
|View full text |Cite
|
Sign up to set email alerts
|

Numerically stable algorithm for discrete-ordinate-method radiative transfer in multiple scattering and emitting layered media

Abstract: We summarize an advanced, thoroughly documented, and quite general purpose discrete ordinate algorithm for time-independent transfer calculations in vertically inhomogeneous, nonisothermal, plane-parallel media. Atmospheric applications ranging from the UV to the radar region of the electromagnetic spectrum are possible. The physical processes included are thermal emission, scattering, absorption, and bidirectional reflection and emission at the lower boundary. The medium may be forced at the top boundary by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
1,914
0
21

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 3,154 publications
(1,947 citation statements)
references
References 14 publications
12
1,914
0
21
Order By: Relevance
“…MODTRAN solves the radiative transfer equation by including the effects of molecular and particulate absorption/emission and scattering, surface reflections and emission, solar/lunar illumination, and spherical refraction. The absorption and scattering processes, considering the atmospheric extinction both for aerosols and molecules, are rigorously calculated using DISORT [60] and Correlated-k [61] algorithms. In addition, MODTRAN uses a spherically symmetric atmosphere, consisting of homogeneous layers, each one characterized by its temperature, pressure and concentration of atmospheric compounds.…”
Section: Modtran5mentioning
confidence: 99%
“…MODTRAN solves the radiative transfer equation by including the effects of molecular and particulate absorption/emission and scattering, surface reflections and emission, solar/lunar illumination, and spherical refraction. The absorption and scattering processes, considering the atmospheric extinction both for aerosols and molecules, are rigorously calculated using DISORT [60] and Correlated-k [61] algorithms. In addition, MODTRAN uses a spherically symmetric atmosphere, consisting of homogeneous layers, each one characterized by its temperature, pressure and concentration of atmospheric compounds.…”
Section: Modtran5mentioning
confidence: 99%
“…Our first modeling approach used the DISORT code of Stamnes et al (1988) in conjunction with snow grain optical properties from Mie theory. This method approximates snow crystals as disconnected spheres and models the reflection of diffuse and directional light by a discrete number of snow layers of finite thickness but infinite in the horizontal direction.…”
Section: Reflectance Modeling At 1310 Nmmentioning
confidence: 99%
“…For example, using the DISORT radiative transfer model of Stamnes et al (1988), we calculated light transmission through the troposphere and in the snowpack, and found that a reduction in SSA of snow from 32 to 16 m 2 kg −1 at the summer solstice at noon, 65 • N, causes an instantaneous forcing of 22 W m −2 at the tropopause, increasing column solar absorption by about 6.5%.…”
Section: Introductionmentioning
confidence: 99%
“…3.4. The 1-D radiative transfer equation is solved by the DIScrete-Ordinate-method Radiative Transfer (DISORT) solver with 32 streams in pseudospherical geometry (Stamnes et al, 1988;Buras et al, 2011;Dahlback and Stamnes, 1991). The radiative transfer model computes both the direct and the multiple scattered diffuse radiation, L(θ, φ).…”
Section: Radiative Transfer Modelmentioning
confidence: 99%